Genetic Transformation and Genomic Resources for Next-Generation Precise Genome Engineering in Vegetable Crops - Cardi, Teodoro; D’Agostino, Nunzio; Tripodi, Pasquale (Frontiers in Plant Science, 2017)
In the frame of modern agriculture facing the predicted increase of population and general environmental changes, the securement of high quality food remains a major challenge to deal with. Vegetable crops include a large number of species, characterized by multiple geographical origins, large genetic variability and diverse reproductive features. Due to their nutritional value, they have an important place in human diet. In recent years, many crop genomes have been sequenced allowing the identification of genes and superior alleles associated with desirable traits. Furthermore, innovative biotechnological approaches provide a step forward in the development of new improved cultivars harboring precise genome modifications. Sequence-based knowledge coupled with advanced biotechnologies is supporting the widespread application of new plant breeding techniques (NPBT) to enhance the success in modification and transfer of useful alleles into target varieties. Clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein 9 (Cas9) system, zinc-finger nucleases (ZFNs) and transcription activator like effector nucleases (TALENs) represent the main methods available for plant genome engineering through targeted modifications. Such technologies, however, require efficient transformation protocols as well as extensive genomic resources and accurate knowledge before they can be efficiently exploited in practical breeding programs. In this review, we revise the state of the art in relation to availability of such scientific and technological resources in various groups of vegetables, describe genome editing results obtained so far and discuss the implications for future applications